ANATOLIAN ESCAPE TECTONICS DRIVEN BY EOCENE CRUSTAL THICKENING AND NEOGENE-QUATERNARY EXTENSIONAL COLLAPSE IN THE EASTERN MEDITERRANEAN REGION - Dhont D.; Chorowicz J.; Luxey P. (My University, 2006)
Tectonic escape is frequently considered to result from compression in a collisional belt, a free boundary opening the way to lateral extrusion of rigid blocks. However, in Anatolia the complex tectonic history provides an opportunity to better understand why a widespread late Cenozoic extension occurs instead of generalized compression. In contrast to common opinion, we argue in this article that the major thickening of the Anatolian plateau did not occur during late Cenozoic times as a consequence of the Africa-Arabia collision with Eurasia and related compression. When examining the distribution of the late Cenozoic deformation in eastern Anatolia, the main argument is that the region was subjected largely to extension and strike-slip tectonics. Compression was limited to the narrow eastern Taurus belt and to a north-south strip comprising the Afsin and Gürün arcs and the Sivas basin. This is shown by a review of the literature and by complementary examination of radar and regional-scale Digital Elevation Model imagery. A second argument is that a major crustal thickening occurred prior to the late Cenozoic during a major collisional event that took place in the Eocene. Crustal thickening was followed by extensional collapse of Anatolia during the Neogene-Quaternary after the opening of the Aegean basin free border during the Oligocene. Consequently, the escape of Anatolia largely implies body forces previously stored in the lithosphere, inducing extensional collapse over crustal-scale detachments, triggered by the onset of a free boundary in the west. This tectonic evolution is related to the progressive propagation of the extension from west to east, which induced eastward propagation of the North Anatolian fault forming the northern boundary of the area submitted to tension. © 2006 Geological Society of America.
Keywords: ANATOLIA; COLLISION; ESCAPE TECTONICS; EXTENSION; RADAR IMAGERY; REMOTE SENSING; Quaternary; Neogene; Oligocene; Eocene; Cenozoic::Quaternary; Кайнозой::Четвертичная; Cenozoic::Neogene; Кайнозой::Неоген; Cenozoic::Paleogene::Oligocene; Кайнозой::Палеоген::Олигоцен; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен